A metal organic framework / molecular sieve composite mixed matrix membrane and its preparation and application
By combining the modified metal organic frame material with molecular sieve and PVDF and other materials, a composite mixed matrix membrane was prepared, which solved the problems of stability and efficiency of existing membranes in toluene/water separation, and achieved high selectivity, high permeability and long-life membrane separation effect.
Patent Information
- Application Number
- CN202411364424.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-29
AI Technical Summary
There are problems with stability and treatment efficiency during the toluene/water separation process, especially the water stability of MOF materials limits the life of the membrane.
By combining metal organic frame (MOF) materials with molecular sieve, and surface modification of MOF materials, the modified MOF materials are mixed with PVDF and other materials together, a metal organic frame/molecular sieve composite mixed matrix membrane is prepared.
It significantly improves the selectivity and permeability of the mixed matrix membrane, extends the service life of the membrane, enhances chemical stability and mechanical strength, and achieves efficient separation of toluene and water.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and relates to a metal organic framework / molecular sieve composite mixed matrix membrane and the preparation and application thereof. Background Art
[0002] In the daily production of chemical, pharmaceutical and environmental engineering industries, a lot of industrial wastewater containing toluene is usually generated. Toluene is one of the volatile organic compounds that is carcinogenic and toxic, and it can harm human health even at very low concentrations. If these wastewaters are not properly separated and purified and directly discharged, it will cause serious damage to the ecological environment.
[0003] Traditional separation methods, such as distillation, extraction and adsorption, often have some unavoidable defects, such as high energy consumption, high operating costs, difficulty in treating low concentrations of pollutants and difficulty in regeneration. Membrane separation technology has attracted widespread attention due to its advantages such as low energy consumption, simple operation and easy large-scale production. In recent years, mixed matrix membranes (MMMs) have become a separation material with application prospects because they combine the advantages of inorganic fillers and organic polymers. This membrane can overcome the shortcomings of low separation performance of pure polymer membranes and high cost of inorganic membranes, but there are still problems with the interfacial compatibility between inorganic fillers and organic polymer matrices and the stability of mixed matrix membranes. In particular, the water stability of some MOF materials limits the life of the obtained mixed matrix membranes, which is also a hot spot and difficulty in current research.
[0004] Therefore, the development of a new type of mixed matrix membrane that can achieve high efficiency, high selectivity and long-term stable membrane separation has important scientific research value and broad industrial application prospects. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a metal organic framework / molecular sieve composite mixed matrix membrane and its preparation and application. By combining the characteristics of metal organic framework (MOF) materials and molecular sieves and modifying inorganic fillers, the separation performance of the mixed matrix membrane for toluene / water system is improved, so as to solve the problems of stability and / or processing efficiency encountered by the mixed matrix membrane in the toluene / water separation process.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane, comprising the following steps:
[0008] (1) weighing a MOF material and a toluene solution of a silane coupling agent, mixing them, refluxing them under an inert atmosphere, and then separating, washing, and drying them to obtain a modified MOF material;
[0009] (2) adding the modified MOF material and the molecular sieve into DMF and mixing them, and then adding PVA (polyvinyl alcohol) and dispersing them evenly to obtain a first solution;
[0010] (3) preparing a DMF solution of PVDF, adding polyethylene glycol under heating and stirring, and adding polyethylene glycol to the first solution after it is dissolved and evenly dispersed, and continuing heating and stirring, ultrasonicating, to obtain a casting solution;
[0011] (4) The casting solution is filtered and poured onto a horizontal glass plate, and then scraped into a film. The film is allowed to stand at room temperature and dried to obtain a mixed matrix membrane, which is the target product.
[0012] Further, in step (1), the MOF material is one of MAF-2, MAF-6, FMOF-1, MIL-101, MIL-53, ZIF-8, ZIF-67, ZIF-71 and ZIF-L, and its particle size is 10-1000nm. Here, the materials such as MAF-2, MAF-6, FMOF-1, MIL-101, MIL-53, ZIF-8, ZIF-67, ZIF-71 and ZIF-L used are conventional commercial products in the art or prepared by conventional techniques, and their particle size is preferably 10-1000nm.
[0013] Furthermore, in step (1), the silane coupling agent is one of 3-chloropropyltrimethoxysilane, vinyltriethoxysilane or vinyltrichlorosilane.
[0014] Furthermore, in step (1), the mass ratio of the silane coupling agent to the MOF material is (5-20):1.
[0015] Furthermore, in step (1), the reflux temperature is 100-300° C. and the time is 1-12 h.
[0016] Furthermore, in step (1), the concentration of the toluene solution of the silane coupling agent is 2-70 wt %, preferably 5-20 wt %.
[0017] Furthermore, the inert atmosphere is argon or the like.
[0018] Furthermore, in step (2), the mass ratio of the modified MOF material to the molecular sieve is (0.1-4):1.
[0019] Furthermore, in step (2), the total mass concentration of the modified MOF material and the molecular sieve in the first solution is 1-50 wt%, and can be 5-20 wt% for example;
[0020] The amount of PVA added satisfies: its concentration in the first solution is 0.1-20wt%. Exemplarily, the amount of PVA added can be 0.1-0.5wt%.
[0021] Furthermore, in step (2), the molecular sieve is one of Silicalite-1, NaY and USY molecular sieves, and its particle size is 1-800 nm, preferably Silicalite-1 molecular sieve.
[0022] The Silicalite-1, NaY and USY molecular sieves herein may be conventional commercial products in the art, or products prepared using conventional techniques.
[0023] Furthermore, in step (2), after adding PVA, heating, stirring and ultrasonic treatment can be used to promote dissolution and dispersion, and the heating temperature can be 80-200°C.
[0024] Furthermore, in step (3), the temperature of heating and stirring is 50-120°C;
[0025] The concentration of the PVDF DMF solution is 10-25wt%, and the amount of polyethylene glycol added is 1-25wt%;
[0026] The mass ratio of the PVDF and the modified MOF material is (4-16):1.
[0027] Furthermore, in step (4), the film thickness is controlled to be 100-500 μm during the film-forming process.
[0028] On the other hand, the present invention also provides a metal organic framework / molecular sieve composite mixed matrix membrane, which is prepared by any of the preparation methods described above.
[0029] In a third aspect, the present invention also provides an application of a metal organic framework / molecular sieve composite mixed matrix membrane in the pervaporation separation of a toluene / water system.
[0030] Furthermore, in a specific application process, the toluene content in the toluene / water mixture is 100-1000 ppm.
[0031] Furthermore, in a specific application process, when the pervaporation method is used for separation, the feed temperature is 20-70°C.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] (1) The mixed matrix membrane prepared by the present invention exhibits significant beneficial effects in the separation process of toluene and water, and significantly improves the service life of the mixed matrix membrane. The surface of the MOF material is pre-modified to enhance the combination of MOF and molecular sieve. At the same time, combined with the introduction of molecular sieve, the selectivity and permeability of the membrane are significantly improved, and effective separation of toluene and water at a higher permeation rate is achieved. In addition, the introduction of molecular sieve (hydrophobicity) effectively improves the hydrophobicity of the membrane, making it more difficult for water molecules to pass through the membrane layer, which can significantly enhance the chemical stability and mechanical strength of the membrane, improve the service life of the membrane, and reduce the replacement frequency and maintenance cost.
[0034] (2) The mixed matrix membrane of the present invention is suitable for the efficient separation of toluene and water. The membrane achieves the preparation of a highly selective and highly permeable separation membrane by adsorbing a hydrophobic molecular sieve layer on the surface of the MOF material, while effectively improving the chemical stability of the MOF-mixed matrix membrane and being able to tolerate higher concentrations of toluene. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0036] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0037] Example 1
[0038] Step 1: First, prepare the MOF material. Dissolve 0.970g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 1.642g of 2-methylimidazole in 50 mL of methanol, treat with an ultrasonic cleaner for 1 hour, and stir and mix at room temperature for 5 hours. Collect the formed purple suspension. Separate the ZIF-67 nanoparticles by centrifugation at 10,000 rpm, wash with ethanol three times, and dry in a vacuum oven at 100°C overnight.
[0039] The ZIF-67 prepared above was mixed with 50 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110°C for 5 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0040] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. Transfer the resulting solution to a 100ml polytetrafluoroethylene hydrothermal kettle, and react the hydrothermal kettle at 105°C for 48h. After heating, cool naturally overnight, and use anhydrous ethanol to repeatedly centrifuge and ultrasonically clean the product until the supernatant is neutral. Collect the centrifuged product and place it in a 100°C oven to dry overnight. The dried product is placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0041] 0.3 g of material A and 0.5 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then kept ultrasonically for standby use to obtain solution C.
[0042] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol thereto, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0043] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a film scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane with a thickness of about 60 μm.
[0044] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance, and the separation test of toluene and water (toluene content of 300ppm) was carried out. Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 47 kg / (m²·h), and the selectivity for toluene reached 450.1 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, after 350 hours of continuous operation test, the separation performance of the membrane remained above 95%, and the separation performance of the membrane did not decrease significantly, showing good stability.
[0045] Example 2
[0046] Step 1: Dissolve 0.9175g Co(NO3)2·6H2O in 60ml methanol to prepare solution A, and then dissolve 2.029g 2-methylimidazole in 60ml methanol to prepare solution B. Place them on a magnetic stirrer and stir until dissolved. Then slowly add solution A to solution B. Seal the beaker with a sealing film and stir for 17 hours. Then centrifuge it (7000 rpm, 10 min) and wash it three times with methanol. Place it in a vacuum drying oven overnight to obtain ZIF-67 (i.e., MOF material).
[0047] The ZIF-67 prepared above was mixed with 70 mL of a 7 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110° C. for 8 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100° C. overnight to obtain material A.
[0048] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. The resulting solution was transferred to a 100ml polytetrafluoroethylene hydrothermal kettle, and the hydrothermal kettle was reacted at 115°C for 48h. After heating, it was cooled naturally overnight, and the product was repeatedly centrifuged and ultrasonically cleaned with anhydrous ethanol until the supernatant was neutral. The centrifuged product was collected and placed in a 100°C oven for overnight drying. The dried product was placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0049] Take 0.3 g of material A and 0.3 g of material B and add them together into 6.2 mL of DMF solution. The mixture is ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA is added thereto. The mixture is heated with stirring at 90° C. for 3 h and ultrasonically treated for 2 h. Then, the ultrasonic treatment is maintained for standby use to obtain solution C.
[0050] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h, then add 0.2 g of polyethylene glycol, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0051] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a 53 μm mixed matrix membrane.
[0052] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 48kg / (m²·h), and the selectivity for toluene reached 403.5 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, the separation performance of the membrane remained above 95% after 280 hours of continuous operation test.
[0053] Example 3
[0054] Step 1: Weigh 0.2g NaOH and dissolve it in 25ml deionized water, take 2.00g zinc nitrate nonahydrate and add it to the above solution, ultrasonicate for 5 minutes, and finally take 0.83g terephthalic acid into the mixed solution. After ultrasonication for 10 minutes, transfer the mixed solution to a polytetrafluoroethylene reactor, heat the reactor to 170℃, react for 24 hours, take out the sample, wash it with DMF six times and then with anhydrous ethanol three times, then centrifuge it, and finally put the sample into a beaker and vacuum dry it overnight to obtain ZIF-8.
[0055] The ZIF-8 prepared above was mixed with 60 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110° C. for 8 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100° C. overnight to obtain material A.
[0056] Step 2: Add 14.50g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. The resulting solution was transferred to a 100ml polytetrafluoroethylene hydrothermal kettle, and the hydrothermal kettle was reacted at 110°C for 48h. After heating, it was cooled naturally overnight, and the product was repeatedly centrifuged and ultrasonically cleaned with anhydrous ethanol until the supernatant was neutral. The centrifuged product was collected and placed in a 100°C oven for overnight drying. The dried product was placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0057] 0.25 g of material A and 0.6 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then maintained for standby use to obtain solution C.
[0058] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h, then add 0.2 g of polyethylene glycol, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0059] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a 77 μm mixed matrix membrane.
[0060] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30°C and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 38kg / (m²·h), and the selectivity for toluene reached 385.7 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, the separation performance of the membrane remained above 95% after 300 hours of continuous operation test.
[0061] Example 4
[0062] Step 1: Weigh 0.2g NaOH and dissolve it in 25ml deionized water, take 2g zinc nitrate nonahydrate and add it to the above solution, ultrasonicate for 5 minutes, and finally take 0.83g terephthalic acid into the mixed solution. After ultrasonication for 10 minutes, transfer the mixed solution to a polytetrafluoroethylene reactor, heat the reactor to 170℃, react for 24 hours, take out the sample, wash it six times with DMF and then wash it three times with anhydrous ethanol, then centrifuge it, and finally put the sample into a beaker and vacuum dry it overnight to obtain ZIF-8.
[0063] The ZIF-8 prepared above was mixed with 60 mL toluene solution of 12 wt% 3-chloropropyltrimethoxysilane, and the mixture was refluxed at 110°C for 8 h under argon environment. The obtained product was centrifuged, washed with ethanol three times, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0064] Step 2: Sodium aluminate was added to water glass, and then the mixture was aged in a sealed static state at room temperature for 24 hours. First, an initial gel directing agent with a molar composition of 10.66 (Na2O): 1 (Al2O3): 9.8 (SiO2): 215 (H2O) was prepared, which means that the molar ratio of Na2O, Al2O3, SiO2, and H2O was 10.66: 1: 9.8: 215. Subsequently, the initial gel directing agent was added to a mixed gel of water glass, sodium aluminate, and water with a molar ratio of 3.3 (Na2O): 1 (Al2O3): 9.8 (SiO2): 200 (H2O). The amount of the directing agent added was 5.8%. The obtained gel was dynamically aged at 80°C for 10 hours, and then dynamically crystallized at 100°C for 22 hours. The obtained sample was washed with distilled water for several times, dried, filtered, and dried at 120°C to obtain material B, namely NaY molecular sieve.
[0065] 0.4 g of material A and 0.1 g of material B were added to 10 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.3 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then maintained for standby use to obtain solution C.
[0066] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h, then add 0.2 g of polyethylene glycol, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain the casting solution.
[0067] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a 61 μm mixed matrix membrane.
[0068] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 63kg / (m²·h), and the selectivity for toluene reached 280.4 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, the separation performance of the membrane remained above 95% after 300 hours of continuous operation test.
[0069] Example 5
[0070] Step 1: First, prepare the MOF material. Add 2.11g of chromium nitrate nonahydrate, 0.88g of terephthalic acid and 80mL of water into the inner tank of the hydrothermal kettle, use an ultrasonic cleaner to treat for 15min, and place it in a 180℃ oven for 6h. The obtained product is centrifuged and dried to obtain MIL-101 nanoparticles with a particle size of 30nm.
[0071] The prepared MIL-101 was mixed with 50 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110°C for 5 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0072] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. Transfer the resulting solution to a 100ml polytetrafluoroethylene hydrothermal kettle, and react the hydrothermal kettle at 105°C for 48h. After heating, cool naturally overnight, and use anhydrous ethanol to repeatedly centrifuge and ultrasonically clean the product until the supernatant is neutral. Collect the centrifuged product and place it in a 100°C oven to dry overnight. The dried product is placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0073] 0.3 g of material A and 0.5 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then kept ultrasonically for standby use to obtain solution C.
[0074] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol thereto, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0075] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a film scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane with a thickness of 43 μm.
[0076] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 18kg / (m²·h), and the selectivity for toluene reached 580.9 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, the separation performance of the membrane remained above 95% after 250 hours of continuous operation test.
[0077] Example 6
[0078] Step 1: First, prepare the MOF material, add 1.06g of chromium nitrate nonahydrate, 0.44g of terephthalic acid, 0.23g of stearic acid and 80mL of water into the inner tank of the hydrothermal kettle, use an ultrasonic cleaner to treat for 15min, and place it in a 180℃ oven for reaction for 6h. The obtained product is centrifuged and dried to obtain MIL-101 nanoparticles with a particle size of 100nm.
[0079] The prepared MIL-101 was mixed with 50 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110°C for 5 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0080] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. Transfer the resulting solution to a 100ml polytetrafluoroethylene hydrothermal kettle, and react the hydrothermal kettle at 105°C for 48h. After heating, cool naturally overnight, and use anhydrous ethanol to repeatedly centrifuge and ultrasonically clean the product until the supernatant is neutral. Collect the centrifuged product and place it in a 100°C oven to dry overnight. The dried product is placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0081] 0.3 g of material A and 0.5 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then kept ultrasonically for standby use to obtain solution C.
[0082] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol thereto, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0083] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane with a thickness of 50 μm.
[0084] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance, and the separation test of toluene and water (toluene content of 300ppm) was carried out. Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 51kg / (m²·h), and the selectivity for toluene reached 381.8 (separation factor), indicating that the membrane has high permeability and high selectivity. At the same time, after 450 hours of continuous operation test, the separation performance of the membrane remained above 95%, and the separation performance of the membrane did not decrease significantly, showing good stability.
[0085] Comparing Example 5 with Example 6, in Example 6, stearic acid was introduced during the preparation of MIL-101 nanoparticles, which can increase the particle size of the prepared MOF material and optimize the morphology accordingly, thereby further improving the flux and stability of the obtained mixed matrix membrane.
[0086] Example 7
[0087] Step 1: First, prepare the MOF material. Add 0.219 g zinc acetate dihydrate to 5 mL methanol and 0.246 g 2-methylimidazole to 5 mL methanol. Mix them after dissolving. Transfer the above solution to a hydrothermal reactor and react in an oven at 100 ° C for 24 hours. After the reaction, ultrasonicate for 10 minutes. The obtained product is centrifuged and dried to obtain ZIF-8 nanoparticles with a particle size of 2 μm.
[0088] The prepared ZIF-8 was mixed with 50 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110°C for 5 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0089] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. Transfer the resulting solution to a 100ml polytetrafluoroethylene hydrothermal kettle, and react the hydrothermal kettle at 105°C for 48h. After heating, cool naturally overnight, and use anhydrous ethanol to repeatedly centrifuge and ultrasonically clean the product until the supernatant is neutral. Collect the centrifuged product and place it in a 100°C oven to dry overnight. The dried product is placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0090] 0.3 g of material A and 0.5 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then kept ultrasonically for standby use to obtain solution C.
[0091] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol thereto, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0092] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane with a thickness of 50 μm.
[0093] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 88 kg / (m²·h), and the selectivity for toluene reached 213.6 (separation factor). After 221 hours of continuous operation test, the separation performance of the membrane remained above 95%.
[0094] Example 8
[0095] Step 1: First, prepare the MOF material. First, add 0.878g zinc acetate dihydrate into 80mL methanol to dissolve it; then take 1.64g 4,5-dichloroimidazole and 0.736g formic acid into another 80mL methanol, put it into a hydrothermal kettle after dissolution, mix it, and react it in an oven at 85℃ for 1h. The obtained product is centrifuged and dried to obtain ZIF-71 nanoparticles with a particle size of 450nm.
[0096] The prepared ZIF-71 was mixed with 50 mL of a 5 wt% 3-chloropropyltrimethoxysilane toluene solution, and the mixture was refluxed at 110°C for 5 h under an argon environment. The obtained product was centrifuged, washed three times with ethanol, and dried in a vacuum oven at 100°C overnight to obtain material A.
[0097] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. Transfer the resulting solution to a 100ml polytetrafluoroethylene hydrothermal kettle, and react the hydrothermal kettle at 105°C for 48h. After heating, cool naturally overnight, and use anhydrous ethanol to repeatedly centrifuge and ultrasonically clean the product until the supernatant is neutral. Collect the centrifuged product and place it in a 100°C oven to dry overnight. The dried product is placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0098] 0.3 g of material A and 0.5 g of material B were added to 6.2 mL of DMF solution, and the mixture was ultrasonically treated for 3 h to ensure uniform mixing. Then 0.1 g of PVA was added thereto, and the mixture was stirred and heated at 90° C. for 3 h, ultrasonically treated for 2 h, and then kept ultrasonically for standby use to obtain solution C.
[0099] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol thereto, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0100] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane with a thickness of 50 μm.
[0101] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 70kg / (m²·h), and the selectivity for toluene reached 304.5 (separation factor). After 230 hours of continuous operation test, the separation performance of the membrane remained above 95%.
[0102] Comparative Example 1
[0103] Step 1: 0.970 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 1.642 g of 2-methylimidazole were dissolved in 50 mL of methanol, treated with an ultrasonic cleaner for 1 hour, and stirred at room temperature for 5 hours. The purple suspension was collected. ZIF-67 nanoparticles were separated by centrifugation at 10,000 rpm, washed with ethanol three times, and dried in a vacuum oven at 100°C overnight to obtain ZIF-67.
[0104] Step 2: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h to obtain a yellow solution, then add 0.2 g of polyethylene glycol and continue stirring for 1 h, finally add 0.14 g of ZIF-67 particles, and ultrasonically treat for 2 h to obtain a casting solution.
[0105] Step 3: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane.
[0106] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 93 kg / (m²·h), and the selectivity for toluene reached 172.3 (separation factor). After testing, the membrane separation performance remained above 95% and could only be operated continuously for about 150 hours.
[0107] Comparative Example 2:
[0108] Step 1: 0.970 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 1.642 g of 2-methylimidazole were dissolved in 50 mL of methanol, treated with an ultrasonic cleaner for 1 hour, and stirred at room temperature for 5 hours. The purple suspension was collected. ZIF-67 nanoparticles were separated by centrifugation at 10,000 rpm, washed with ethanol three times, and dried in a vacuum oven at 100°C overnight to obtain ZIF-67.
[0109] Step 2: Take 0.14 g of ZIF-67 and add it to 6.2 mL of DMF solution. Ultrasonicate the mixture for 3 h to ensure uniform mixing. Then add 0.1 g of PVA, stir and heat at 90°C for 3 h, ultrasonicate for 2 h, and keep ultrasonicating for standby use to obtain solution A.
[0110] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h, then add 0.2 g of polyethylene glycol and continue stirring for 1 h to obtain solution B, add solution A to solution B, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain the casting solution.
[0111] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a mixed matrix membrane.
[0112] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 72kg / (m²·h), and the selectivity for toluene reached 232.6 (separation factor). The membrane could only run continuously for about 170 hours under the condition that the separation performance was maintained above 95%.
[0113] In addition, comparing Comparative Example 1 with Comparative Example 2, the addition of PVA mainly improves the interfacial compatibility between MOF and the substrate, thereby reducing defects, and ultimately resulting in a decrease in flux but an increase in selectivity.
[0114] Comparative Example 3
[0115] Step 1: Dissolve 0.9175 g Co(NO3)2·6H2O in 60 ml methanol to prepare solution A, and then dissolve 2.029 g 2-methylimidazole in 60 ml methanol to prepare solution B. Place them on a magnetic stirrer and stir until dissolved. Then slowly add solution A to solution B. Seal the beaker with a sealing film and stir for 17 hours. Then centrifuge it (7000 rpm, 10 min) and wash it three times with methanol. Place it in a vacuum drying oven overnight to obtain material A, i.e., ZIF-67.
[0116] Step 2: Add 14.41g of deionized water, 10.00g of 25% tetrapropylammonium hydroxide (TPAOH) aqueous solution, 10.89g of tetraethyl orthosilicate (TEOS) and 9.44g of anhydrous ethanol to a plastic wide-mouth bottle and stir for 3h at room temperature to mix evenly. The resulting solution was transferred to a 100ml polytetrafluoroethylene hydrothermal kettle, and the hydrothermal kettle was reacted at 115°C for 48h. After heating, it was cooled naturally overnight, and the product was repeatedly centrifuged and ultrasonically cleaned with anhydrous ethanol until the supernatant was neutral. The centrifuged product was collected and placed in a 100°C oven for overnight drying. The dried product was placed in a 500°C muffle furnace for 12h to obtain material B, i.e., Silicalite-1 molecular sieve.
[0117] 0.3 g of material A and 0.3 g of material B were added into 6.2 mL of DMF solution, and the mixture was sonicated for 3 h to ensure uniform mixing. The sonication was maintained for standby use to obtain solution C.
[0118] Step 3: Take 1.3 g of PVDF and add it to 6.2 mL of DMF, stir and heat at 60°C for 2 h, then add 0.2 g of polyethylene glycol, ultrasonically treat for 1 h to obtain solution D, add solution D to solution C, heat and stir at 60°C for 3 h, and finally ultrasonically treat the obtained solution for 2 h to obtain a casting solution.
[0119] Step 4: Pour the casting solution through the filter screen onto a dry and clean horizontal glass plate at room temperature and cast it into a film using a scraper. After the film is left to stand at room temperature, it is dried in a vacuum oven at 60°C for 48 h to obtain a 53 μm mixed matrix membrane.
[0120] The prepared mixed matrix membrane was installed in a membrane separation device to evaluate the membrane separation performance and to conduct a separation test of toluene and water (toluene content of 300ppm). Under the feed conditions of 30℃ and 1 bar, the test results showed that the total flow rate of toluene / water mixed solution passing through the membrane was 80kg / (m²·h), and the selectivity for toluene reached 86.2 (separation factor). After testing, the membrane separation performance remained above 95% and could only be operated continuously for about 190 hours.
[0121] Comparing Example 2 with Comparative Example 3, it can be seen that when the MOF material is not surface modified, the selectivity and stability of the subsequently prepared mixed matrix membrane are significantly reduced.
[0122] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane, characterized in that: The following steps are involved: (1) weighing a MOF material and a toluene solution of a silane coupling agent, mixing them, refluxing them under an inert atmosphere, and then separating, washing, and drying them to obtain a modified MOF material; (2) adding the modified MOF material and the molecular sieve into DMF and mixing them, then adding PVA and dispersing them evenly to obtain a first solution; (3) preparing a DMF solution of PVDF, adding polyethylene glycol under heating and stirring, and adding polyethylene glycol to the first solution after it is dissolved and evenly dispersed, and continuing heating and stirring, ultrasonicating, to obtain a casting solution; (4) Filter the casting solution and pour it onto a horizontal glass plate, scrape it into a film, let it stand at room temperature, and dry it to obtain a mixed matrix membrane, which is the target product; The MOF material is one of MIL-101, ZIF-8, ZIF-67 and ZIF-71, and its particle size is 10-1000nm; The molecular sieve is one of Silicalite-1 and NaY, and its particle size is 1-800nm; In step (1), the silane coupling agent is one of 3-chloropropyltrimethoxysilane, vinyltriethoxysilane or vinyltrichlorosilane.
2. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (1), the mass ratio of the silane coupling agent to the MOF material is (5-20):
1.
3. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (1), the reflux temperature is 100-300°C and the time is 1-12h.
4. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (2), the mass ratio of the modified MOF material to the molecular sieve is (0.1-4): 1; The total mass concentration of the modified MOF material and the molecular sieve in the first solution is 1-50 wt %.
5. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (2), the amount of PVA added satisfies: its concentration in the first solution is 0.1-20 wt %.
6. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (3), the temperature of heating and stirring is 50-120°C; The concentration of the PVDF DMF solution is 10-25wt%, and the amount of polyethylene glycol added is 1-25wt%; The mass ratio of the PVDF and the modified MOF material is (4-16):
1.
7. The method for preparing a metal organic framework / molecular sieve composite mixed matrix membrane according to claim 1, characterized in that: In step (4), the film thickness is controlled to be 100-500 μm during the film-forming process.
8. A metal organic framework / molecular sieve composite mixed matrix membrane, prepared by the preparation method according to any one of claims 1 to 7.
9. Use of a metal organic framework / molecular sieve composite mixed matrix membrane as claimed in claim 8 in pervaporation separation of toluene / water system.
Citation Information
Patent Citations
Porous granule MCM-41-ZIF-8 / PDMS pervaporation hybrid membrane, preparation and application
CN103816814A
Flow processing and characterization of metal-organic framework (MOF) membranes in hollow fiber and tubular modules
US20140336435A1